Pathogenic Chlamydia Lack a Classical Sacculus but Synthesize a Narrow, Mid-cell Peptidoglycan Ring, Regulated by MreB, for Cell Division - Liechti, George (PLoS Pathog, 2016)
The peptidoglycan (PG) cell wall is a peptide cross-linked glycan polymer essential for bacterial division and maintenance of cell shape and hydrostatic pressure. Bacteria in the Chlamydiales were long thought to lack PG until recent advances in PG labeling technologies revealed the presence of this critical cell wall component in Chlamydia trachomatis. In this study, we utilize bio-orthogonal D-amino acid dipeptide probes combined with super-resolution microscopy to demonstrate that four pathogenic Chlamydiae species each possess a ≤ 140 nm wide PG ring limited to the division plane during the replicative phase of their developmental cycles. Assembly of this PG ring is rapid, processive, and linked to the bacterial actin-like protein, MreB. Both MreB polymerization and PG biosynthesis occur only in the intracellular form of pathogenic Chlamydia and are required for cell enlargement, division, and transition between the microbe’s developmental forms. Our kinetic, molecular, and biochemical analyses suggest that the development of this limited, transient, PG ring structure is the result of pathoadaptation by Chlamydia to an intracellular niche within its vertebrate host.